COVID-19: Perspectives From Frontline Critical Care Nurses in New York. Issue 3 (July 2021) - Saputo, Mary; Maloney, Mary; Ohler, Linda
Abstract : New York City quickly became the epicenter of coronavirus disease-2019 (COVID-19) in early March of 2020. While hospitals were aware of the potential of COVID-19, the volume of critically ill patients that flooded the hospitals in the New York City area was clearly not anticipated. Hospital staff worked quickly to create COVID-19-free areas, but were overcome with the volume of COVID-positive critically ill patients. Many newly admitted patients required respiratory support with mechanical ventilation. As Governor Cuomo issued executive orders to stay at home in mid-March, some patients were afraid to go into hospitals despite symptoms of respiratory distress. Once these patients came to the hospital, they were often critically ill. Emergency departments and intensive care units filled rapidly, overwhelming staff and equipment needs with such things as pumps, dialysis machines, medications, and personal protective equipment. Plans for the day were disrupted with frequent rapid response calls and the need for additional beds. Key issues that confronted the COVID-19 response in critical care units at NYU Langone Health included communication, patient and staff safety.